Passing the Buck: Transferring Social and Cultural Capital in an Employment Preparation Program - Ralf St.Clair (Adult Education Research Conference, 2000)
This case study examines influences on curriculum in the employment preparation provision of a trade union in British Columbia. Analysis illustrates the importance of forces external to the immediate educational setting, the most pervasive being the requirement to function as an effective means of transferring cultural and social capital to unemployed people.